Implementasi Model Project Based Learning (PJBL) Dalam Menumbuhkan Minat Belajar Siswa Pada Pembelajaran Pendidikan Agama Hindu dan Budi Pekerti di SMP Negeri 5 Sukawati - Ni Putu Divayanti Utami; Si Luh Nyoman Seriadi; Kadek Dedy Herawan (Yayasan Madinah Al-Aziziyah, 2026)
Hindu Religious Education and Character Education have an important role in shaping students’ character and spirituality. However, students’ learning interest in the learning process is still relatively low, as indicated by the lack of participation and enthusiasm during classroom activities. This study aims to analyze the implementation of the Project Based Learning (PjBL) model in fostering students’ learning interest in Hindu Religious Education and Character Education at SMP Negeri 5 Sukawati. This research used a qualitative descriptive approach. The subjects of the study consisted of the principal, vice principal of curriculum, Hindu Religious Education teachers, and eighth-grade students. Data were collected through observation, interviews, documentation, and literature study. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the PjBL model was able to increase students’ active participation through project-based activities and collaborative learning. Supporting factors included the role of teachers, adequate school facilities, and students’ enthusiasm in learning. Meanwhile, the inhibiting factors included limited learning time, differences in students’ abilities, and limited facilities. Efforts made to overcome these obstacles were carried out through structured planning, intensive guidance, and optimal utilization of available facilities. Therefore, the implementation of PjBL can create a more active, meaningful, and enjoyable learning atmosphere for students.